Soil-boron equilibrium reactions - Pavan, Marcos Antonio; Correa, Antonio Elias (Pesquisa Agropecuaria Brasileira, 2014)
Boron adsorption characteristics of selected acid soils from Paraná State, Brazil, were evaluated. Equilibrium concentration between soluble B and adsorbed B is consistent with a mechanism described by the Langmuir equation, except that deviations occur at solution concentration greater than 4 mg/l of B. Soils showed variation in their B-adsorption capacity. The maximum B-adsorption capacity of soils was little sensible under pH less than 6.5 but increased markedly in pH between 6.5 to 8.0. Adsorbed boron in the alkaline pH range was released by reacidification to the original soil pH, indicating the reversibility of the fixation reaction. The constant "b" values derived from the Langmuir equation increased with increasing the clay and organic matter content of soils.